The Development of Yoruba Candomble Communities in Salvador, Bahia, 1835–1986 - Alonso, Miguel C.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2014)
This project is an attempt to bring together the many fragments of history concerning the Yoruba religious community and their rise to prominence in Salvador, Bahia, Brazil, from the mid-nineteenth to the late-twentieth centuries.
Keywords: Ethnography; Religion and sociology; Ethnology-Africa.; Religion; Anthropology; Social history; Ethnography; Sociology of Religion; African Culture; Religious Studies, general; Anthropology; Social History